DETERMINAN PERSEPSI HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - Tamrin, Moh; Tukinah, Ukie; Putri, Devi Amelia (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to determine the relationship between price perception, product quality, and service quality to customer satisfaction in Mixue Genuksari Semarang City. The population in the study was Mixue Genuksari Semarang City customers. The sampling technique used is incidental sampling with a sample of 100 respondents. Data collection was carried out using questionnaires with Likert scales. The analysis method used in this study is a multiple linear regression analysis method with SPSS 23 application. The results of research based on the t Test, namely H1, show that price perception has a significant effect on customer satisfaction with a significant value of 0.005 < 0.05. H2 shows that product quality has a significant effect on customer satisfaction with a significant value of 0.000 < 0.05. H3 shows that service quality has a significant effect on customer satisfaction with a significant value of 0.000 < 0.05. And based on the results of the value of the coefficient of determination (R2) which shows that the variables of price perception, product quality, and service quality affect customer satisfaction by 72.5%, and the remaining 27.5% are influenced by other variables outside the model. The results of the study partially independent variables consisting of price perception, product quality, and service quality have a positive and significant effect on customer satisfaction in Mixue Genuksari Semarang City. For future research, it is recommended to use other variables that affect customer satisfaction that are not yet in this study, extend the observation time, and increase the number of samples.